Pharmacy PT. X Summarecon Bekasi in the market penetration of non -prescription drug products as a new pharmacy - Atikah, Hibatul Wafi; Saragi, Sahat; Putriana, Lies (Science Midwifery, 2024)
Pharmacies are health service facilities as a place to distribute pharmaceutical supplies which are required to be able to survive in changing business conditions, especially new pharmacies. The aim of this research is to determine the effectiveness of market penetration of non-prescription medicinal products at PT Pharmacy. Dr. X Summarecon Bekasi in returning investments within the time period specified in the Feasibility Study. This research method is quantitative-descriptive and observation from 4 perspectives of the balanced scorecard method. The data collection tool used is an instrument in the form of a Google form. The results of this research can be concluded that the Pharmacy PT. X Summarecon Bekasi as a new pharmacy in the market penetration of non -prescription drug products observed using the Balanced Scorecard method shows the results of "good" and able to restore investment in the time set in the feasibility study, which is within 4 years and 8 months.